Analisis Ratio Solvabilitas Dan Profitabilitas Untuk Tahun 2018-2020 Pada UD. Rubama Kabupaten Tapanuli Tengah - Rahmadani Manik; Safriadi Pohan; Tiurlina Hasmawati Sihite (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
Financial ratio analysis is one way to assess a company's financial performance. This research aims to determine the financial performance of UD. Rubama. The research uses financial management theory based on measuring instruments Debt to Assets Ratio, Debt to Equity ratio, Return On Investment and Return On Equity. The approach used in this research is a descriptive research approach. The samples in this research are UD's balance sheet and profit and loss report. Rubama for the 3 year period 2018-2020. The data analysis technique used in this research is descriptive data analysis technique, namely collecting data, classifying it in such a way as to obtain a clear picture of the facts that exist as a reality in the object under study. The research results show that the company's financial performance as measured by the solvency ratio (Debt to Assets Ratio) and (Debt to Equity Ratio) is good, because there is an increase in the amount of debt and is followed by an increase in the amount of assets every year and the company is able to emphasize funding using its own capital. The results of the profitability ratio analysis show that the company's ability to generate profits in terms of Return on Investment is good, because the profits are quite high in terms of asset turnover. Meanwhile, in terms of Return On Equity, the company is also good because the company has not been able to maximize its capital to produce optimal net profits, the average during the research period was 36%.